[n]‐Cyclo‐9, 9‐dibutyl‐2, 7‐fluorene (n=4, 5): Nanoring Size Influence in Carbon‐Bridged Cyclo‐para‐phenylenes. (30th April 2020) - Sicard, Lambert; Lucas, Fabien; Jeannin, Olivier; Bouit, Pierre‐Antoine; Rault‐Berthelot, Joëlle; Quinton, Cassandre; Poriel, Cyril
Abstract: For the last ten years, ring‐shaped π‐conjugated macrocycles possessing radially directed π‐orbitals have been subject to intense research. The electronic properties of these rings are deeply dependent on their size. However, most studies involve the flagship family of nanorings: the cyclo‐ para ‐phenylenes. We report herein the synthesis and study of the first examples of cyclofluorenes possessing five constituting fluorene units. The structural, optical and electrochemical properties were elucidated by X‐ray crystallography, UV‐vis absorption and fluorescence spectroscopy, and cyclic voltammetry. By comparison with a shorter analogue, we show how the electronic properties of [5]‐cyclofluorenes are drastically different from those of [4]‐cyclofluorenes, highlighting the key role played by the ring size in the cyclofluorene family. Abstract : Nanorings : The first examples of cyclofluorenes possessing five constituting fluorene units were synthesized and studied. The electronic properties of [5]‐cyclofluorenes are drastically different from those of [4]‐cyclofluorenes, highlighting the key role played by the ring size in the cyclofluorene family.